Biocompatible implant surface treatments - Bikash Pattanaik; Sudhir Pawar; Seema Pattanaik (Wolters Kluwer Medknow Publications, 2012)
Surface plays a crucial role in biological interactions. Surface treatments have been applied to metallic biomaterials in order to improve their wear properties, corrosion resistance, and biocompatibility. A systematic review was performed on studies investigating the effects of implant surface treatments on biocompatibility. We searched the literature using PubMed, electronic databases from 1990 to 2009. Key words such as implant surface topography, surface roughness, surface treatment, surface characteristics, and surface coatings were used. The search was restricted to English language articles published from 1990 to December 2009. Additionally, a manual search in the major dental implant journals was performed. When considering studies, clinical studies were preferred followed by histological human studies, animal studies, and in vitro studies. A total of 115 articles were selected after elimination: clinical studies, 24; human histomorphometric studies, 11; animal histomorphometric studies, 46; in vitro studies, 34. The following observations were made in this review: The focus has shifted from surface roughness to surface chemistry and a combination of chemical manipulations on the porous structure. More investigations are done regarding surface coatings.Bone response to almost all the surface treatments was favorable.Future trend is focused on the development of osteogenic implant surfaces. Limitation of this study is that we tried to give a broader overview related to implant surface treatments. It does not give any conclusion regarding the best biocompatible implant surface treatment investigated till date. Unfortunately, the eventually selected studies were too heterogeneous for inference of data.